The use of Macrophytes as indicators of heavy metals in aquatic ecosystems - Shaharuddin, Ruhul Izzati; Mohd Latiff, Nur Hanie; Wan Muhamad, Wan Naimatul Asiah; Othman, Rashidi (2012)
Macrophytes are excellent indicators of environmental quality due to the variety of ways in which they respond to anthropogenic pollution. In environmental impact studies, certain plant species provide valuable information about the chemical state of their environment through their presence. The study focused on assesment of trace element contamination in fresh water bodies where nine different aquatic plant species were abundant and dominant. All the water samples were analyzed for iron (Fe), lead (Pb), copper (Cu), zinc (Zn), nickel (Bi) and manganese (Mn) contamination. Based on the result, the abundance of certain aquatic species indicates high concentration of certain heavy metal within critical range in that particular environment. H.verticillata and B. Bucifera are good indicator for Pb. S. Batans and C. Fuscata indicate high concentration of Fe and Cu. Besides, Zn showed high concentration with C. Fuscata and H. Verticillata. E. Crassipes good indicator for Bi and Mn. The concentrations of metals in aquatic plants can be more than 100 000 times greater than in the associated water. Therefore, macrophyte is effective in responding to heavy metal in low level environmental contamination that might otherwise be difficult to detect.